Stable nitrogen removal in the novel continuous flow anammox system under deteriorated partial nitrification: Significance and superiority of the anaerobic-oxic-anoxic–oxic operation mode. (October 2022) - Feng, Yan; Wang, Shuying; Peng, Yongzhen
Graphical abstract: Highlights: NAR decreased while the portion of TIN removed by anammox in anoxic zone increased. TIN in influent and effluent were 50.1 and 8.7 mg/L, respectively with C/N of 3.3. Total HRT decreased 4 h and aerobic HRT was 3.75 h in the steady operation period. EPDA in the anoxic zone ensured nitrogen removal with capacity of 0.098 kg N/m 3 ·d. Regardless of the NAR, the nitrogen removal in the AOAO process was robust. Abstract: The collapse of mainstream anammox system caused by deterioration of partial nitrification (PN) is easy to occur and it is vital to quickly restore the stable nitrogen elimination performance. Herein, a novel continuous push-flow anaerobic-oxic-anoxic–oxic (AOAO) process treating sewage was used to restore the nitrogen elimination performance rapidly under deteriorated PN. The increased abundances of Nitrospira and Candidatus Nitrotoga was responsible for the deterioration of PN. Effluent total inorganic nitrogen of 8.7 mg N/L and a stable nitrogen removal rate of 0.083 kg N/m 3 ·d were obtained with the aerobic hydraulic retention time (HRT) of 3.75 h even PN deteriorated. Endogenous partial denitrification coupled anammox in the anoxic zone was essential to maintain stable nitrogen removal under the deterioration of PN and the anammox contribution increased from 17.2 % to 23.6 %. The AOAO system shows robustness on nitrogen removal even PN deteriorated under the decrease of HRT from 16 to 12 h.